H-bonding supramolecular interactions driving the dispersion of kaolin into benzoxazine: A tool for the reinforcement of polybenzoxazines thermal and thermo-mechanical properties. (6th April 2015) - Ganfoud, Rime; Puchot, Laura; Fouquet, Thierry; Verge, Pierre
Abstract: The network structure of polybenzoxazines is known to be supported by strong inter- and intra-molecular hydrogen bonds. Kaolin, a platelet clay mineral, possesses similar supramolecular interactions, preventing its platelets from exfoliation when mixed with polymers. In the present study, demonstration of the ability of 3, 3′-ethane-1, 2-diylbis(3, 4-dihydro-2H-1, 3-benzoxazine) (EDBZ) to assembly onto kaolin surface through hydrogen bonding is given by Fourier transform infrared spectroscopy (FTIR). Composites were subsequently prepared by a convenient solventless method, leading to high performance materials with improved thermal and thermo-mechanical properties. As the improvement of the thermo-mechanical properties could be due to a catalytic effect of the clay interlayer cations, Sepiolite – a mineral clay with a similar cation exchange capacity than kaolin but with a far lower OH group content – was used to prepared composites. Similar crosslinking kinetics of EDBZ are obtained for composites prepared with either kaolin or sepiolite. However the dispersion state of sepiolite is disastrous, whereas kaolin is finely dispersed thanks to its higher OH group content, highlighting the predominant role of H-bonding interactions onto kaolin dispersion within EDBZ.